PERFORMANCE OF HIGHER EDUCATION TO REALIZE SUPERIOR HIGHER EDUCATION: A SYSTEMATIC STUDY OF THE LITERATURE REVIEW - Suyitno Suyitno (Dynamic Management Journal, 2026)
This research aims to synthesize performance indicators of higher education institutions in order to realize superior higher education. The approach used is Systematic Literature Review (SLR) with the PRISMA 2020 protocol, covering 44 scientific articles selected from leading international databases in the range of 2015–2025. The analysis was carried out thematically and narrativeally to identify, classify, and map performance indicators from various institutional perspectives. The results of the study revealed five main interrelated domains of performance indicators, namely: (1) academic professional identity, (2) institutional effectiveness, (3) institutional managerial structure, (4) organizational culture, and (5) behavioral ambidexterity. These five indicators form an integrative conceptual model that represents the complexity of internal relations in modern higher education. This model emphasizes that the performance of an institution cannot be judged solely from the quantity of academic output, but must consider the social, psychological, and structural dimensions of the academic actors within it. This study emphasizes the importance of a multidimensional and reflective approach in the institutional evaluation of higher education. This research also contributes to the development of a more contextual and participatory evaluation model, as well as provides a theoretical basis for more humanistic and sustainable institutional reform.